Odpowiedź :
Temat: Rozwiązywanie równań
Rozwiązania poniżej ;-)
- a)
(x + 3)(x + 5) = -4(x² + 2) + 5x²
x² + 5x + 3x + 15 = -4x² - 8 + 5x²
x² + 8x + 15 = x² - 8
x² + 8x - x² = -8 - 15
8x = -23 / : 8
x = -2 i 7/8
- b)
(x - 2)(4 + x) = x(x - 5)
4x + x² - 8 - 2x = x² - 5x
4x + x² - 2x - x² + 5x = 8
7x = 8 / : 7
x = 1 i 1/7
- c)
-2x(x + 1) = (3 - 2x)(x + 2)
-2x² - 2x = 3x + 6 - 2x² - 4x
-2x² - 2x - 3x + 2x² + 4x = 6
-x = 6 / : (-1)
x = -6
- d)
(x - 3)(x + 3) = (x - 2)²
x² - 9 = x² - 4x + 4
x² - x² + 4x = 4 + 9
4x = 13 / : 4
x = 3 i 1/4
a)
[tex](x+3)(x+5) = -4(x^{2} +2) +5x^{2} =\\x^{2} + 5x + 3x + 15 = -4x^{2} - 8 + 5x^{2} =\\8x = -23\\x = -\frac{23}{8}[/tex]
b)
[tex]-2x(x+1) = (3 - 2x)(x+2) =\\-2x^{2} - 2x = 3x +6 -2x^{2} - 4x =\\-x = 6\\x = -6[/tex]
c)
[tex](x-2)(4+x) = x(x-5) =\\4x + x^{2} - 8 - 2x = x^{2} - 5x =\\9 x =-8\\x = - \frac{8}{9}[/tex]
d)
[tex](x -3)(x+3)= (x-2)^{2} =\\x^{2} +3x - 3x - 9 = x^{2} -4x +4 =\\-13 = -4x\\x = - \frac{13}{4}[/tex]